If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5x+26=13x-39
We move all terms to the left:
5x+26-(13x-39)=0
We get rid of parentheses
5x-13x+39+26=0
We add all the numbers together, and all the variables
-8x+65=0
We move all terms containing x to the left, all other terms to the right
-8x=-65
x=-65/-8
x=8+1/8
| |7r-3|=|4r+15| | | 16d+9=7d+45 | | 8a=12=44a= | | 5(3y)=15 | | 3c-12=3c= | | 4y+21=37y= | | 10+5=2g-1 | | 5b-11=59b= | | -2y^2=-162 | | 5x^2=-320 | | 3a-5+a=6a+5-2a | | 3a-5+a=6@+5-2a | | 7(2-3d)=56 | | -60-9n=5+3n | | P(x)=75x-500 | | -7-4v=8v+60 | | 3x2=3 | | 23x^2=19 | | 2y^2=-162 | | 7z+8=2z-26 | | 5(r-3)=2(r+6) | | √x-4=1 | | 2(x+3)-(x-2)=5 | | 8w+12=3w+46 | | 6-3x=5-7x | | 6y+12=2y-34 | | 50-3v=2v+5 | | 3y-5y+11=17 | | 2z+5=4z-15 | | 4y+5=5y-12 | | 7x-1=x-1 | | 3+7v+8=-17 |